HUBUNGAN PERILAKU MEROKOK ORANG TUA DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI UPTD PUSKESMAS TABANAN III: RELATIONSHIP OF PARENTS SMOKING BEHAVIOR WITH THE EVENT OF ACUTE RESPIRATORY INFECTION IN INFANTS AT TABANAN UPTD PUSKESMAS III - Wahyuni, Ni Made Heni; Mirayanti, Ni Ketut Ayu; Eka Sari, Niken Ayu Merna (Bali Medika Jurnal, 2020)
The Acute Respiratory Infection contributes 16% from all children death at the age of under five years which cause the the death on 920.136 children under five years . Occurrence of Acute Respiratory Infection of the children under 5 years is caused by demographic factor, biological factor,and pollution factor in the form of smoking behavior. The expose of cigarette smoke to the children from their parents makes them are exposed to dangerous smoke which can disturb their respiratory. The aim of this research is to determine the correlation between smoking behavior with the incidence of acute respiratory infection of infant at UPTD Puskesmas Tabanan III. The design of this research is analytic correlation with cross sectional. The number of samples are 68 children under five years by using purposive sampling. The data was collected by questionnaire and observation and analyzed by statistical test Chi Square. The result shows from 68 respondents 75% of parents are smokers and the number of incidence of acute respiratory infections of children under 5 years is 63,2% The result of this analysis shows there is a correlation between smoking behavior of parents with the incidence of acute respiratory infection infants at UPTD Puskesmas Tabanan III. It is suggested healh officers to raise activities to socialize and educate about the danger of smoking cigarettes to the children under 5 years.